EFEKTIVITAS PENGGUNAAN ABSEN FINGER PRINT UNTUK MENINGKATKAN DISIPLIN KARYAWAN DI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MULIA BALIKPAPAN - Endah Lestari (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2024)
The use of fingerprint timesheets makes it easier for the Faculty of Business Economics (FEB) at Mulia University to monitor employee discipline regarding work entry and leaving times, and makes it easier to record employee attendance data online. Employees whose attendance exceeds 8.15 am are considered late, and will receive sanctions such as a deduction from the employee's transportation allowance. Even though there is already the use of fingerprint absences and sanctions for being late, there are still employees who show up late. This research aims to provide information regarding the effectiveness of implementing fingerprint absences at FEB Mulia University. This research uses descriptive qualitative research to provide an overview based on facts about the object under study. Data collection was carried out by interviewing various sources and observing the use of fingerprint absences at FEB. The results of this research provide information that the use of finger print attendance has been effective for FEB, because it reduces the use of paper (paperless), takes faster time to retrieve data from the finger print machine to Excel, reduces the risk of incorrect data recaps and increases employee attendance discipline. The use of fingerprint absences also experiences obstacles such as difficulty detecting fingerprints, resulting in repeated absences, susceptible to didisease transmission and expensive investment costs.